Wizerunek jako przesłanka kreowania produktu. Próba konstrukcji nowego modelu produktu - Cieloch, Grzegorz (Image as a Premise of Product's Creating. An Attempt of Forming a New Model of Product, 2006)
Theoretical model of product as an element of marketing mix has several limitations and disadvantages. This article is an attempt to express a new structure of marketing product. This new model is based on technological and marketing elements. It is compatible with many theoretical solutions concerning product itself, its value and development. The author gives some examples of practical use of theoretical solutions proposed by himself. The new model is adopted to the service sector requirements as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 70-83